Brief History of English and American Literature - Beers, Henry A. (Henry Augustin), 1847-1926 (Salt Lake City, UT : Project Gutenberg, 2007)
"Brief History of English and American Literature" by Henry A. Beers is a historical account written in the late 19th century. This work aims to provide a comprehensive overview of the development of literature in England and America, spanning significant authors, works, and literary movements. Beers emphasizes the impact of various historical and cultural forces on literary expression, exploring how the literature reflects the changing society. The opening of the book provides an introduction by John Fletcher Hurst, who outlines the importance of studying literature, especially for ministers and students of religious history. It emphasizes that the pursuit of literary knowledge is essential for an understanding of human thought and cultural aspirations. Hurst highlights a methodical approach to studying literature, suggesting the need to categorize writers by their periods, styles, and influences. While Beers' overview will ultimately touch upon various forms and periods in literature, the introduction focuses on establishing a groundwork for understanding the organizational structure of the literary history to follow. (This is an automatically generated summary.)
Release date is 2007-04-15
E-text prepared by Al Haines
Keywords: American literature -- History and criticism; English literature -- History and criticism; English-speaking countries -- Intellectual life